Team-Based Learning: a randomized clinical trial in undergraduate nursing - Sakamoto, Sabrina Ramires [UNESP]; Queiroz Dell'Acqua, Magda Cristina [UNESP]; Fernandes Abbade, Luciana Patricia [UNESP]; Caldeira, Silvia Maria [UNESP]; Benato Fusco, Suzimar de Fatima [UNESP]; Garcia de Avila, Marla Andreia [UNESP] (Assoc Brasileira Enfermagem, 2020)
Objectives: To compare the knowledge on surgical safety through the team-based learning methodology and lecture classes for undergraduate Nursing students, and evaluate the learning satisfaction with team-based learning. Methods: Randomized, controlled, parallel, two-arm, unblinded clinical trial developed in the Faculty of Medicine of a public university in Botucatu, Brazil. The groups included 14 students for team-based learning and 11 students for lecture classes. Results: Students' apprehension of knowledge in the team-based learning group was significantly higher compared to the control group (p<0.002) by considering the pre-test results. After 30 days, there was no significant difference between groups. The experience with the methodology was considered positive among students. Conclusions: Team-based learning is an important pedagogic tool available and has proven effective in education and learning with students playing the role of protagonists.
Keywords: Validation Studies; Nursing; Randomized Controlled Clinical Trial; Higher Education; Patient Safety